Abordagem centrada na atividade para decisões tecnológicas: estudo de caso em cooperativas de catadores de materiais recicláveis - Souza, Renato Luvizoto Rodrigues de (2019)
Since the emergence of recyclable waste pickers’ organizations in the 1990s, these organizations have been responsible for helping in closing the gap left by the public service in waste collection and sorting. Despite the representativeness of the activities developed by these cooperatives and associations in terms of environmental and social aspects, few efforts are made by the public service to provide better facilities, equipment and working conditions to these organizations. This research is focused on the challenges faced for the structuring of waste pickers’ organizations so that they can develop their activities considering productive efficiency and health criteria. In this setting, this research is framed by the following question: how can one incorporate the real work of operators in the technological decisions of waste pickers’ cooperatives? From this question, the goal of this research was to investigate the origins and uses of technologies in collectors’ cooperatives to develop approaches to support the incorporation of the activity in the technological decisions in waste pickers’ cooperatives. Two case studies in two cooperatives were conducted following the theoretical standpoint of the Activity Ergonomics, in which emphasis is placed in the distance between the task and the activity. In this stage the main focus of observations were the artifacts and instruments used materials handling and the facilities, aiming to achieve a better understanding on how the facilities and artifacts were planned and acquired, how the technological adaptations were carried out and workers’ usage of these resources in daily operations. The data show that due to the lack of participation on technological decisions, cooperatives need to adequate spaces, flows and workstations, besides using improvised artifacts as a way to achieve production goals. As outcomes from these aspects and focusing on the technological decisions associated to the facilities and artifacts were developed: a diagnosis tool for decisions planning that enables waste pickers’ organizations to understand their current and future development stages and an articulation between the activity-centered approach and participatory design approaches that enable not only the analysis of the current activity, but also the incorporation of the activity in future work systems design by means of collective decision processes. Furthermore, the structuring of waste pickers’ organizations must be aligned with the demands and specificities of these organizations. In addition, the understanding of the work actually performed at these enterprises and the participation of the involved actors in the decision processes ate the main requirements of the technological decision process.